Epigenetic restriction of Hippo signaling by MORC2 underlies stemness of hepatocellular carcinoma cells. Issue 12 (December 2018) - Wang, Tao; Qin, Zhong-yi; Wen, Liang-zhi; Guo, Yan; Liu, Qin; Lei, Zeng-jie; Pan, Wei; Liu, Kai-jun; Wang, Xing-wei; Lai, Shu-jie; Sun, Wen-jing; Wei, Yan-ling; et al.
Abstract The evolutionarily conserved Hippo signaling pathway is a key regulator of stem cell self-renewal, differentiation, and organ size. While alterations in Hippo signaling are causally linked to uncontrolled cell growth and a broad range of malignancies, genetic mutations in the Hippo pathway are uncommon and it is unclear how the tumor suppressor function of the Hippo pathway is disrupted in human cancers. Here, we report a novel epigenetic mechanism of Hippo inactivation in the context of hepatocellular carcinoma (HCC). We identify a member of the microrchidia (MORC) protein family, MORC2, as an inhibitor of the Hippo pathway by controlling upstream Hippo regulators, neurofibromatosis 2 (NF2 ) andkidney and brain protein (KIBRA ). Mechanistically, MORC2 forms a complex with DNA methyltransferase 3A (DNMT3A) at the promoters ofNF2 andKIBRA, leading to their DNA hyper-methylation and transcriptional repression. As a result, NF2 andKIBRA are crucial targets of MORC2 to regulate confluence-induced activation of Hippo signaling and contact inhibition of cell growth under both physiological and pathological conditions. The MORC2-NF2/KIBRA axis is critical for maintaining self-renewal, sorafenib resistance, and oncogenicity of HCC cells in vitro and in nude mice. Furthermore, MORC2 expression is elevated in HCC tissues, associated with stem-like properties of cancer cells, and disease progression in patients. Collectively, MORC2 promotes cancer stemness and tumorigenesis by facilitating DNA methylation-dependent silencing of Hippo signaling and could be a potential molecular target for cancer therapeutics.